Eksistensi Tokoh Adat Dalam Penyelesaian Sengketa Tanah (LEGAL DIALOGICA, 2025)
This study aims to determine and analyze the existence of the Tu'a Golo traditional figure in resolving land disputes in the indigenous people of Boleng District, Manggarai Bara Regency, East Nusa Tenggara. To determine and understand the factors that influence the resolution of land disputes in the Tu'a Golo traditional figure in the indigenous people of Boleng District.This study uses an empirical legal research type. The location of the research is in the Customary Law area of ​​Boleng District, West Manggarai Regency, East Nusa Tenggara Province. The types and sources of data are Primary and Secondary Data obtained through interview and documentation techniques, then qualitative analysis is carried out.The results of the study show that the existence of the traditional figure Tu'a Golo in the process of resolving land disputes in the traditional community of Boleng District, West Manggarai Regency, East Nusa Tenggara was resolved by Tu'a Golo as a traditional figure. The factors that influence the process of resolving land disputes in the traditional figure Tu'a Golo in the traditional community of Boleng District are internal factors from Tu'a Golo himself and external factors from the community.The recommendation of this study is that Tua Golo conduct socialization of the applicable customary law so that the community prioritizes resolving social and cultural problems through deliberation and consensus. As the customary leader or Hatoe Kampoh, Tu'a Golo always pays attention to his traditional community by being a fair mediator so that he is not influenced by any party.Abstrak:Penelitian ini bertujuan, Untuk mengetahui dan menganalisis Eksitensi tokoh adat Tu’a Golo dalam penyelesaian sengketa Tanah pada masyarakat adat Kecamatan Boleng,Kabupaten Manggarai Bara, Nusa Tenggara Timur. Untuk mengetahui dan memahami Faktor-faktor yang memengaruhi penyelesaian sengketa Tanah di tokoh adat Tu’a Golo pada masyarakat adat Kecamatan Boleng.Penelitian ini menggunakan tipe penelitian Hukum empiris. Lokasi penelitian di wilayah Hukum Adat Kecamatan Boleng, Kabupaten Manggarai Barat, Provinsi Nusa Tenggara Timur. Jenis dan sumber data yaitu Data Primer dan Sekunder yang diperoleh melalui Teknik wawancara dan Dokumentasi, selanjutnya dilakukan analisis secara kualitatif.Hasil penelitian menunjukan, eksistensi tokoh adat Tu’a Golo dalam proses penyelesaian sengketa Tanah pada masyarakat adat Kecamatan Boleng,Kabupaten Manggarai Barat, Nusa Tenggara Timur di selesaikan oleh Tu’a Golo sebagai tokoh adat. faktor-faktor yang memengaruhi proses penyelesaian sengketa Tanah di tokoh adat Tu’a Golo pada masyarakat adat Kecamatan Boleng adalah faktor internal dari Tu’a Golo sendiri dan faktor eksternal dari masyarakat tersebut.Rekomendasi penelitian ini, Agar Tua Golo melakukan sosialisasi terhadap hukum adat yang berlaku supaya masyarakat memprioritaskan penyelesaian masalah sosial dan budaya melalui musyawarah mufakat. sebagai ketua adat atau Hatoe kampoh, Tu'a Golo selalu memperhatikan masyarakat adatnya dengan menjadi penengah yang adil sehingga tidak dipengaruhi oleh pihak manapun.